In Vitro Evaluation of Anti Inflammatory Activity of Methanolic And Ethanolic Leaf Extract of Psidium Guajava (World Journal of Current Medical and Pharmaceutical Research, 2020)
The objective of the current research work was to determine the anti inflammatory activity of Psidium guajava by the Human Red Blood Cell membranes stabilization method. The methanol and ethanol leaf extract of plant Psidium guajava were investigated for their invitro anti-inflammatory property by Human red blood cell membrane stabilization method. The prevention of hypotonocity induced HRBC membrane lysis was taken as a measure of a anti-inflammatory activity. The anti inflammatory activity of methanol and ethanol leaf extract of psidium guajava were compared to that of standard drug Diclofenac.